High-strength elastic composite aerogel and preparation method thereof
By designing a high-strength elastic composite aerogel, using specific raw materials and processes to build a centripetal structure and supramolecular system, the problem of insufficient strength of existing materials is solved, high specific modulus and recovery speed are achieved, and suitable for high Impact and high intensity applications.
Patent Information
- Application Number
- CN202411669362.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
The existing elastic composite aerogel materials have insufficient strength and cannot meet the needs of high impact and high strength application scenarios.
By designing a high-strength elastic composite aerogel, using graphene oxide, polyvinyl alcohol, cellulose nanofibers, aminosilane and tert-butanol as the main raw materials, the centripetal structure is constructed by the ice template method, and the nanofibers are passed The covalent interlock with the silane forms a strong supramolecular system.
It achieves high specific modulus and good recovery speed of composite aerogel, and is competent for high impact and high strength application scenarios, and has the advantages of safety and stability, simple production process and outstanding material performance.
Smart Images

Figure CN119505457A_ABST
Abstract
Description
[Technical field]
[0001] The invention belongs to the technical field of composite materials, and particularly relates to a high-strength elastic composite aerogel and a preparation method thereof. [Background technology]
[0002] Composite aerogels have rapidly become a research hotspot in the fields of aerospace, intelligent sensing, energy, and environmental protection due to their ultra-lightness, low thermal conductivity, high specific surface area, and excellent mechanical properties. A large number of studies have focused on improving the elasticity of aerogels by producing reversible deformations in the structure, but have ignored the resistance of the structure itself to external stress, resulting in elastic aerogels generally exhibiting low modulus characteristics, which cannot meet the wide range of needs in actual application scenarios.
[0003] It is not easy to solve the mechanical property problem of aerogel's own structure. Using centripetal freeze-casting to enhance strength is an effective method. The unique negative Poisson's ratio of the centripetal structure helps to increase the packing density, thereby achieving the purpose of enhancing mechanical properties. However, due to the properties of the substrate itself, the improvement in strength through the structure is very limited. It is necessary to carry out interface engineering design of the interaction force of the material at the molecular scale, and realize the supramolecular system of deformation and resistance coupling through the synergistic effect of composite nanomaterials and centripetal structures.
[0004] Therefore, how to design high-strength supramolecules with toughness is a difficult problem that needs to be solved urgently in order to achieve both elasticity and high modulus. [Summary of the invention]
[0005] In view of the above, it is necessary to provide a high-strength elastic composite aerogel and a preparation method thereof. The composite aerogel prepared by this method has excellent specific modulus and good recovery speed, and can be competent for high-impact and high-strength application scenarios.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A high-strength elastic composite aerogel is mainly made of the following raw materials in parts by weight: 1-3 parts of graphene oxide, 7-10 parts of polyvinyl alcohol, 5-7 parts of cellulose nanofibers, 10-15 parts of aminosilane and 20-25 parts of tert-butyl alcohol.
[0008] Cellulose nanofiber (CNF) is a filamentous cellulose fiber with a diameter of 5-20 nm and a length of several hundred nanometers to several tens of micrometers. The cellulose nanofiber used in the present invention is prepared by a mechanical method.
[0009] Among the raw materials used in the present invention, the graphene oxide powder is multilayer graphene oxide prepared by an improved Hummer method, and the purity is 99wt%; the degree of polymerization of polyvinyl alcohol is 1750±50, and the purity is 99wt%; tert-butyl alcohol serves as a solvent for freeze drying, and the purity is 99.5wt%.
[0010] In the present invention, further, the composite aerogel is mainly made of the following raw materials in parts by weight: 2 parts of graphene oxide, 8 parts of polyvinyl alcohol, 6 parts of cellulose nanofibers, 12 parts of aminosilane and 22 parts of tert-butyl alcohol.
[0011] The present invention also provides a method for preparing the above-mentioned high-strength elastic composite aerogel, the method comprising the following steps:
[0012] (1) preparing a polyvinyl alcohol solution: adding polyvinyl alcohol to deionized water, heating in a water bath and stirring until completely dissolved, to obtain a polyvinyl alcohol solution for later use;
[0013] (2) preparing a graphene oxide dispersion: placing graphene oxide in deionized water, and dispersing the graphene oxide in deionized water by magnetic stirring and ultrasonic treatment at room temperature to obtain a graphene oxide dispersion for later use;
[0014] (3) preparing a cellulose nanofiber suspension: preparing the cellulose nanofibers prepared by the mechanical method into a suspension with a purity of 1 wt % for later use;
[0015] (4) Mixing and freezing treatment: The graphene oxide dispersion, polyvinyl alcohol solution and cellulose nanofiber suspension are mixed uniformly by magnetic stirring, and then aminosilane is added, and then subjected to magnetic stirring and ultrasonic dispersion treatment, followed by a water bath to promote the cross-linking reaction, and then tert-butyl alcohol is added by magnetic stirring, and then poured into a mold and frozen to obtain a suspension;
[0016] (5) Freeze drying and baking: The suspension obtained in step (4) is freeze dried, and then placed in a tubular furnace, heated to 240°C at a rate of 4-6°C / min in a nitrogen atmosphere, and maintained for 3-5 hours to finally obtain a strong and elastic composite aerogel.
[0017] In the present invention, further, in the step (1), the mass ratio of polyvinyl alcohol to deionized water is 1:16-22, and the temperature of the water bath heating is 85-95°C.
[0018] In the present invention, further, the mass ratio of graphene oxide to deionized water in step (2) is 1:90-100.
[0019] In the present invention, further, the magnetic stirring time of step (2) and step (4) is 25-30 minutes, and the ultrasonic dispersion treatment of step (4) is carried out by an ultrasonic crusher at a power of 300 W, at a frequency of turning on for 1 second and turning off for 1 second, for 25-30 minutes.
[0020] In the present invention, further, the aminosilane is N-aminoethyl-3-aminopropylmethyldimethoxysilane, and the purity is 96wt%.
[0021] In the present invention, further, the mold material in step (4) is one of silica gel, polytetrafluoroethylene and copper. The size of the mold is (mm) 20*15*10.
[0022] In the present invention, further, in the step (4), the freezing treatment temperature is -75°C and the freezing time is 25-35 minutes.
[0023] In the present invention, further, the freeze drying in step (5) is performed at a temperature of -75°C and a vacuum degree of less than 20 Pa for 48 hours.
[0024] The present invention has the following beneficial effects:
[0025] In order to solve the technical problems such as insufficient strength of elastic composite aerogel materials, the present invention provides a high-strength elastic composite aerogel and a preparation method thereof. The method of the present invention prepares a negative Poisson's ratio composite aerogel designed with a centripetal structure and a synergistic supramolecular system. Specifically, among the components, cellulose nanofibers and polyvinyl alcohol are used as the supporting skeleton of the composite aerogel, aminosilane is used as a nanofiber crosslinker to achieve the solidification of the skeleton, tert-butyl alcohol can make the nanofibers form uniform and fine pores during the freeze-drying process, improve the filtration performance, and graphene oxide can wrap the fiber skeleton to enhance the elastic recovery rate; in the preparation method, the ice template method constructs a centripetal structure with negative Poisson's ratio characteristics, and forms a strong supramolecular system through covalent interlocking between nanofibers and silane. Its unique features include that aminosilane acts as an adhesive between nanofibers by penetration, participates in the hydrogen bond self-assembly process inside the fiber skeleton that is about to be entangled with each other, and aminosilane and graphene oxide will further cover and wrap the hydroxyl groups on the surface of the fiber skeleton to form rigid fibers, which are used to replace the brittle connection between silane nanoparticles. Then, the ice template method was used to densify the supramolecular skeleton through ice crystal stress to form a secondary framework, and then the centripetal growth of ice crystals was driven by temperature gradient to shape the centripetal topological network structure based on the supramolecular system, giving CR-CAPG a unique negative Poisson's ratio effect. Ultimately, the coupling effect between resistance and deformation can be achieved.
[0026] Through this synergistic strategy, the resulting composite aerogel has excellent specific modulus and recovery speed, and is capable of high impact and high strength application scenarios. This method has the advantages of safety and stability, simple production process and outstanding material performance.
Brief Description of the Drawings
[0027] Figure 1 It is a schematic diagram of the main process of the method for preparing the high-strength elastic composite aerogel of the present invention. [Specific implementation method]
[0028] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific implementation disclosed below.
[0029] Embodiment 1:
[0030] This embodiment provides a high-strength elastic composite aerogel, which is mainly made of the following raw materials in parts by weight: 1 part of graphene oxide, 7 parts of polyvinyl alcohol, 5 parts of cellulose nanofibers, 10 parts of aminosilane and 20 parts of tert-butyl alcohol. The aminosilane is N-aminoethyl-3-aminopropylmethyldimethoxysilane.
[0031] This embodiment also provides a method for preparing the above-mentioned high-strength elastic composite aerogel, such as Figure 1 As shown, the specific steps include:
[0032] (1) preparing a polyvinyl alcohol solution: adding polyvinyl alcohol to deionized water in a mass ratio of 1:16, heating in a water bath at 85° C. and stirring until completely dissolved, to obtain a polyvinyl alcohol solution for later use;
[0033] (2) preparing a graphene oxide dispersion: placing graphene oxide in deionized water, wherein the mass ratio of graphene oxide to deionized water is 1:90, and performing magnetic stirring and ultrasonic dispersion treatment at room temperature to obtain a graphene oxide dispersion for later use;
[0034] (3) preparing a cellulose nanofiber suspension: preparing the cellulose nanofibers prepared by the mechanical method into a suspension with a purity of 1 wt % to obtain a cellulose nanofiber suspension for later use;
[0035] (4) Mixing and freezing treatment: Take the graphene oxide dispersion, polyvinyl alcohol solution and cellulose nanofiber suspension, mix them evenly by magnetic stirring, then add aminosilane, and perform magnetic stirring and ultrasonic dispersion treatment, then perform water bath to promote crosslinking reaction, then add tert-butyl alcohol by magnetic stirring, and then pour into a mold, freeze at a temperature of -75°C, and freeze for 25 minutes to obtain a suspension; the mold material is one of silicone, polytetrafluoroethylene and copper. The size of the mold is (mm) 20*15*10.
[0036] (5) Freeze drying and baking: freeze drying the suspension obtained in step (4) at a temperature of -75°C and a vacuum degree of less than 20 Pa for 48 hours, then placing it in a tubular furnace, heating it to 240°C at a rate of 4°C / min in a nitrogen atmosphere, and maintaining it for 5 hours, to finally obtain a strong and elastic composite aerogel;
[0037] The magnetic stirring time of step (2) and step (4) is 25 minutes, and the ultrasonic dispersion treatment of step (4) is carried out by using an ultrasonic crusher at a power of 300 W, with a frequency of turning on for 1 second and turning off for 1 second, for 25 minutes.
[0038] Embodiment 2:
[0039] This embodiment provides a high-strength elastic composite aerogel, which is mainly made of the following raw materials in parts by weight: 2 parts of graphene oxide, 8 parts of polyvinyl alcohol, 6 parts of cellulose nanofibers, 12 parts of aminosilane and 22 parts of tert-butyl alcohol. The aminosilane is N-aminoethyl-3-aminopropylmethyldimethoxysilane.
[0040] This embodiment also provides a method for preparing the above-mentioned high-strength elastic composite aerogel, such as Figure 1 As shown, the specific steps include:
[0041] (1) preparing a polyvinyl alcohol solution: adding polyvinyl alcohol to deionized water in a mass ratio of 1:19, heating in a water bath at 90° C. and stirring until completely dissolved, to obtain a polyvinyl alcohol solution for later use;
[0042] (2) preparing a graphene oxide dispersion: placing graphene oxide in deionized water, wherein the mass ratio of graphene oxide to deionized water is 1:99, and performing magnetic stirring and ultrasonic dispersion treatment at room temperature to obtain a graphene oxide dispersion for later use;
[0043] (3) preparing a cellulose nanofiber suspension: preparing the cellulose nanofibers prepared by the mechanical method into a suspension with a purity of 1 wt % to obtain a cellulose nanofiber suspension for later use;
[0044] (4) Mixing and freezing treatment: Take the graphene oxide dispersion, polyvinyl alcohol solution and cellulose nanofiber suspension, mix them evenly by magnetic stirring, then add aminosilane, and perform magnetic stirring and ultrasonic dispersion treatment, then perform water bath to promote crosslinking reaction, then add tert-butyl alcohol by magnetic stirring, and then pour into a mold, freeze at a temperature of -75°C, and freeze for 30 minutes to obtain a suspension; the mold material is one of silica gel, polytetrafluoroethylene and copper. The size of the mold is (mm) 20*15*10.
[0045] (5) Freeze drying and baking: freeze drying the suspension obtained in step (4) at a temperature of -75°C and a vacuum degree of less than 20 Pa for 48 hours, then placing it in a tubular furnace, heating it to 240°C at a rate of 5°C / min in a nitrogen atmosphere, and maintaining it for 4 hours, finally obtaining a strong and elastic composite aerogel;
[0046] The magnetic stirring time of step (2) and step (4) is 30 minutes, and the ultrasonic dispersion treatment of step (4) is carried out by using an ultrasonic crusher at a power of 300 W, with a frequency of turning on for 1 second and turning off for 1 second, for 30 minutes.
[0047] Embodiment 3:
[0048] This embodiment provides a high-strength elastic composite aerogel, which is mainly made of the following raw materials in parts by weight: 3 parts of graphene oxide, 10 parts of polyvinyl alcohol, 7 parts of cellulose nanofibers, 15 parts of aminosilane and 25 parts of tert-butyl alcohol. The aminosilane is N-aminoethyl-3-aminopropylmethyldimethoxysilane.
[0049] This embodiment also provides a method for preparing the above-mentioned high-strength elastic composite aerogel, such as Figure 1 As shown, the specific steps include:
[0050] (1) preparing a polyvinyl alcohol solution: adding polyvinyl alcohol to deionized water in a mass ratio of 1:22, heating in a water bath at 95° C. and stirring until completely dissolved, to obtain a polyvinyl alcohol solution for later use;
[0051] (2) preparing a graphene oxide dispersion: placing graphene oxide in deionized water, wherein the mass ratio of graphene oxide to deionized water is 1:100, and performing magnetic stirring and ultrasonic dispersion treatment at room temperature to obtain a graphene oxide dispersion for later use;
[0052] (3) preparing a cellulose nanofiber suspension: preparing the cellulose nanofibers prepared by the mechanical method into a suspension with a purity of 1 wt % to obtain a cellulose nanofiber suspension for later use;
[0053] (4) Mixing and freezing treatment: Take the graphene oxide dispersion, polyvinyl alcohol solution and cellulose nanofiber suspension, mix them evenly by magnetic stirring, then add aminosilane, and perform magnetic stirring and ultrasonic dispersion treatment, then perform water bath to promote crosslinking reaction, then add tert-butyl alcohol by magnetic stirring, and then pour into a mold, freeze at -75°C for 25-35 minutes to obtain a suspension; the mold material is one of silicone, polytetrafluoroethylene and copper. The size of the mold is (mm) 20*15*10.
[0054] (5) Freeze drying and baking: freeze drying the suspension obtained in step (4) at a temperature of -75°C and a vacuum degree of less than 20 Pa for 48 hours, then placing it in a tubular furnace, heating it to 240°C at a rate of 6°C / min in a nitrogen atmosphere, and maintaining it for 3 hours, to finally obtain a strong and elastic composite aerogel;
[0055] The magnetic stirring time of step (2) and step (4) is 27 minutes, and the ultrasonic dispersion treatment of step (4) is carried out by using an ultrasonic crusher at a power of 300 W, with a frequency of turning on for 1 second and turning off for 1 second, for 27 minutes.
[0056] Effect verification:
[0057] In order to further illustrate the effect of the present application, the applicant conducted comparative tests in groups to test the performance of the composite aerogels obtained by using each group of methods. The groups are as follows:
[0058] Group 1: removing aminosilane, and other methods are the same as those in Example 2;
[0059] The second group: the raw material composition of the composite aerogel was changed to include: 2 parts of graphene oxide, 8 parts of polyvinyl alcohol, 6 parts of cellulose nanofibers, 4 parts of aminosilane and 22 parts of tert-butyl alcohol, and the other methods were the same as those in Example 2;
[0060] The third group: the raw material composition of the composite aerogel was changed to include: 2 parts of graphene oxide, 8 parts of polyvinyl alcohol, 6 parts of cellulose nanofibers, 8 parts of aminosilane and 22 parts of tert-butyl alcohol, and the other methods were the same as those in Example 2;
[0061] Group 4: The raw material composition of the composite aerogel was changed to include: 2 parts of graphene oxide, 8 parts of polyvinyl alcohol, 6 parts of cellulose nanofibers, 11 parts of aminosilane and 22 parts of tert-butyl alcohol. Other methods were the same as those in Example 2.
[0062] Group 5: composite aerogel prepared by the method described in Example 2;
[0063] Group 6: The raw material composition of the composite aerogel was changed to include: 2 parts of graphene oxide, 8 parts of polyvinyl alcohol, 6 parts of cellulose nanofibers, 13 parts of aminosilane and 22 parts of tert-butyl alcohol. Other methods were the same as those in Example 2.
[0064] The density (g / cm 3 ), load limit pressure (KPa) and specific strength (kN·m / kg), the results are shown in Table 1:
[0065] Table 1 Comparison of performance of each group of composite aerogels
[0066]
[0067] According to the results in Table 1, the composite aerogel prepared by the method of the present application has excellent performance. Comparing the results of the first to sixth groups, it is found that the raw material composition with different ratios has a very significant effect on the strength of the elastic composite aerogel. The effect is positively correlated, and there is an optimal ratio. When the aminosilane exceeds the ratio, the elastic composite aerogel will break at 233KPa. After obtaining the fifth group with the best ratio, the applicant further tested other indicators of the fifth group of composite aerogels and found that its porosity was about 90%, and it could withstand a maximum pressure of 5.5Mpa without structural damage. After withstanding 1000 cycles of compression at 50% strain, it maintained a similar strain-stress curve, and the stress retention rate was still as high as 88.7%, the height was only lost by 12.5%, and the recovery rate was 792mm s -1 , indicating that the composite aerogel prepared by the method of the present application exhibits ultra-lightness, high porosity, good fatigue resistance and extremely high strength.
[0068] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-strength elastic composite aerogel, characterized in that: The composite aerogel is mainly made of the following raw materials in parts by weight: 1-3 parts of graphene oxide, 7-10 parts of polyvinyl alcohol, 5-7 parts of cellulose nanofibers, 10-15 parts of aminosilane and 20-25 parts of tert-butyl alcohol.
2. The elastic composite aerogel according to claim 1, characterized in that: The composite aerogel is mainly made of the following raw materials in parts by weight: 2 parts of graphene oxide, 8 parts of polyvinyl alcohol, 6 parts of cellulose nanofibers, 12 parts of aminosilane and 22 parts of tert-butyl alcohol.
3. A method for preparing a high-strength elastic composite aerogel according to any one of claims 1-2, characterized in that: The method comprises the following steps: (1) preparing a polyvinyl alcohol solution: adding polyvinyl alcohol to deionized water, heating in a water bath and stirring until completely dissolved, to obtain a polyvinyl alcohol solution for later use; (2) preparing a graphene oxide dispersion: placing graphene oxide in deionized water, and dispersing the graphene oxide in deionized water by magnetic stirring and ultrasonic treatment at room temperature to obtain a graphene oxide dispersion for later use; (3) preparing a cellulose nanofiber suspension: preparing the cellulose nanofibers into a suspension with a purity of 1 wt % for later use; (4) Mixing and freezing treatment: The graphene oxide dispersion, polyvinyl alcohol solution and cellulose nanofiber suspension are mixed uniformly by magnetic stirring, and then aminosilane is added, and then subjected to magnetic stirring and ultrasonic dispersion treatment, followed by a water bath to promote the cross-linking reaction, and then tert-butyl alcohol is added by magnetic stirring, and then poured into a mold and frozen to obtain a suspension; (5) Freeze drying and baking: The suspension obtained in step (4) is freeze dried, and then placed in a tubular furnace, heated to 240°C at a rate of 4-6°C / min in a nitrogen atmosphere, and maintained for 3-5 hours to finally obtain a strong and elastic composite aerogel.
4. The method according to claim 3, characterized in that In the step (1), the mass ratio of polyvinyl alcohol to deionized water is 1:16-22, and the temperature of the water bath heating is 85-95°C.
5. The method according to claim 1, characterized in that In the step (2), the mass ratio of graphene oxide to deionized water is 1:90-100.
6. The method according to claim 3, characterized in that The magnetic stirring time of step (2) and step (4) is 25-30 minutes, and the ultrasonic dispersion treatment of step (4) is carried out by using an ultrasonic crusher at a power of 300 W, with a frequency of turning on for 1 second and turning off for 1 second, for 25-30 minutes.
7. The method according to claim 3, characterized in that The aminosilane is N-aminoethyl-3-aminopropylmethyldimethoxysilane.
8. The method according to claim 3, characterized in that The mold material in step (4) is any one of silicone, polytetrafluoroethylene and copper.
9. The method according to claim 3, characterized in that: In the step (4), the freezing treatment temperature is -75°C and the freezing time is 25-35 minutes.
10. The method according to claim 3, characterized in that The freeze drying in step (5) is performed at a temperature of -75°C and a vacuum degree of less than 20 Pa for 48 hours.
Citation Information
Cited By
Negative Poisson's ratio auxetic toughening hydrogel material and preparation method and application thereof
CN120574439A